Methodical approach to teaching students mechanisms of hemoblastosis development at the department of pathophysiology - A. M. Yelinska (Kazimierz Wielki University, 2021)
This work is a fragment of the initiative research "The role of transcription factors, the circadian oscillator system and metabolic disorders in the formation and functioning of pathological systems" (№ 0119U103898). The article is devoted to the problem of methodical approach to teaching the topic "Hemoblastosis" at the Department of Pathophysiology. Module 2 "Pathophysiology of organs and systems" begins with the study of the submodule "Pathophysiology of the blood system" for all students majoring in 222 "Medicine", 228 "Pediatrics" and 221 "Dentistry". One of the difficult topics for students to understand is the topic of "Hemoblastosis". InUkraine, the system of higher medical education is undergoing active innovative changes. This process is characterized by the introduction of new technologies and techniques in the educational process. Innovative forms and methods of teaching are developed and implemented. The purpose of this work is to analyze the difficulties that students have when they studying the topic of "Hemoblastosis" and the development of methodological approaches to their elimination. According to the WHO: cancer is one of the leading causes of death in the world: in 2012, there were 8.2 million deaths from cancer. Hemoblastosis accounts for approximately 8% of all malignancies and all together they are among the 6 most common types of malignant tumors. Acute leukemias account for about 50-60% of all leukemias, with acute myeloblastic leukemia being slightly more common than acute lymphoblastic leukemia. Chronic leukemias account for about 40-50% of all leukemias, with chronic lymphocytic leukemia being slightly more common than chronic myelocytic leukemia. Hemoblastosis is a relatively rare disease; mortality from them is 1.7-3.1 per 100,000 population. Among therapeutic diseases, leukemia occurs in 1.5-2.6% of cases. Recently, the incidences of hemoblastosis, especially acute, have increased in all countries.